(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Depression is state of low mood and loss of interest in usual activities,which results in cognitive dysfunction like learning and memory impairment,affect behavior pattern of person.In the present study flavonoid rich ethanol extract of Neolamarcki acadamba (NcEe) and Abrus precatorious (ApEe) leaves was evaluated for antidepressant potential in different animal models like Forced swim test in rat (r-FST),mice tail suspension test (m-TST) and Reserpine Induced Hypothermia in Rat(r-RIH). Imipramine (15mg/kg,i.p.) was used as standard drug and reserpine (2 mg/kg,s.c.) in reserpine induced depression in rat.Duration of immobility was examined in rat forced swim test and mice tail suspension test.Rectal temperature was noted in reserpine induced hypothermia in rat.In RIH animal model rectal temperature along with ptosis was examined. In this experiment, Imipramine, NcEe and ApEe extract significantly reduced duration of immobility in both r-FST and m-TST as compare to control group. ApEe extract (Flavonoid) showed significant decrease in duration of immobility time in behavioral model of rat and mice at dose 200mg/kg and 400mg/kg ,p.o. In reserpine induced hypothermia model, ApEe extract showed significant reversal of hypothermia which induced by reserpine in dose dependent manner at dose 200mg/kg and 400mg/kg, p.o. NcEe extract (Flavonoid) shows significant decrease in duration of immobility time in behavioral model and significantly showed reversal of hypothermia in reserpine induced hypothermia model at high dose (400mg/kg) as compare to vehicle and imipramine (standard) treated group.